Assembly, structure and thermoelectric properties of 1, 1′-dialkynylferrocene 'hinges'. Issue 28 (4th July 2022) - Wilkinson, Luke A.; Bennett, Troy L. R.; Grace, Iain M.; Hamill, Joseph; Wang, Xintai; Au-Yong, Sophie; Ismael, Ali; Jarvis, Samuel P.; Hou, Songjun; Albrecht, Tim; Cohen, Lesley F.; Lambert, Colin; et al.
Abstract : Dialkynylferrocenes are interesting candidates for molecular electronics. Herein, numerous experiments are applied to probe their properties both as single-molecules and in monolayers, demonstrating unique geometric and thermoelectric properties. Abstract : Dialkynylferrocenes exhibit attractive electronic and rotational features that make them ideal candidates for use in molecular electronic applications. However previous works have primarily focussed on single-molecule studies, with limited opportunities to translate these features into devices. In this report, we utilise a variety of techniques to examine both the geometric and electronic structure of a range of 1, 1′-dialkynylferrocene molecules, as either single-molecules, or as self-assembled monolayers. Previous single molecule studies have shown that similar molecules can adopt an 'open' conformation. However, in this work, DFT calculations, STM-BJ experiments and AFM imaging reveal that these molecules prefer to occupy a 'hairpin' conformation, where both alkynes point towards the metal surface. Interestingly we find that only one of the terminal anchor groups binds to the surface, though both the presence and nature of the second alkyne affect the thermoelectric properties of these systems. First, the secondary alkyne acts to affect the position of the frontier molecular orbitals, leading to increases in the Seebeck coefficient. Secondly, theoretical calculations suggested that rotating the secondary alkyne away from the surface acts to modulate thermoelectric properties. This work represents the first of its kind to examine the assembly of dialkynylferrocenes, providing valuable information about both their structure and electronic properties, as well as unveiling new ways in which both of these properties can be controlled.